Peptide boronic acids by late-stage hydroboration on the solid phase - Werner, Marius; Brinkhofer, Julian; Hammermüller, Leon; Heim, Thomas; Pham, Truc Lam; Huber, Jonas; Klein, Christian D.; Thomas, Franziska (Advanced science, 2024)
Organoboron compounds have a wide range of applications in numerous research fields, and methods to incorporate them in biomolecules are much sought after. Here, on-resin chemical syntheses of aliphatic and vinylogous peptide boronic acids are presented by transition metal-catalyzed late-stage hydroboration of alkene and alkyne groups in peptides and peptoids, for example on allyl- and propargylglycine residues, using readily available chemicals. These methods yield peptide boronic acids with much shorter linkers than previously reported on-resin methods. Furthermore, the methods are regio- and stereoselective, compatible with all canonical amino acid residues and can be applied to short, long, and in part even “difficult” peptide sequences. In a feasibility study, the protected peptide vinylboronic acids are further derivatized by the Petasis reaction using salicylaldehyde derivatives. The ability of the obtained peptide boronic acids to reversibly bind to carbohydrates is demonstrated in a catch-release model experiment using a fluorescently labeled peptide boronic acid on cross-linked dextran beads. In summary, this highlights the potential of the target compounds for drug discovery, glycan-specific target recognition, controlled release, and diagnostics.